2015
DOI: 10.1097/sap.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Outcomes From the Use of Fibrin Sealant for Fixation of Skin Grafts in Small-Size Burns Compared to Staples as Historical Controls

Abstract: The use of fibrin sealants allows for fewer graft loss complications and earlier discharge in patients who have burns that are less than 10% TBSA. This decrease in hospital days results in savings, although this difference is not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Gibran and co‐workers reported 100 per cent graft survival in both groups on day 14 ( P = 0·352). Although mentioned in the methods, Butts et al . did not report rates of complete wound closure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gibran and co‐workers reported 100 per cent graft survival in both groups on day 14 ( P = 0·352). Although mentioned in the methods, Butts et al . did not report rates of complete wound closure.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies considered graft loss. Butts et al . reported significantly lower graft loss rates in the fibrin glue group (less than 1 per cent versus 4 per cent for control; P = 0·03).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In skin grafting, graft fixation is important. Use of sutures or staples is a standard method for skin fixation (Zederfeldt 1994; Waiker and Shinalingappa 2015; Butts et al 2015); however, the use of fibrin glue has also been suggested. Use of fibrin as an adhesive was introduced by Bergel in 1909, and Tidrick and Warner used fibrin for skin graft fixation for the first time in 1944 (Saltz et al 1991).…”
Section: Introductionmentioning
confidence: 99%